Functional production of clostridial circularin A in Lactococcus lactis NZ9000 and mutational analysis of its aromatic and cationic residues - Liu, Fangfang; van Heel, Auke J.; Chen, Jingqi; Kuipers, Oscar P. (Frontiers in Microbiology, 2022)
Circular bacteriocins, also known as bacterial head-to-tail cyclized peptides, are a subgroup of ribosomally synthesized and post-translationally modified peptides (RiPPs). Compared with their conventional linear counterparts, circular bacteriocins are highly stable over a broad temperature and pH range, and circularization decreases proteolytic degradation by exopeptidases. These features render them great potential as scaffold candidates to withstand strident conditions in food- and pharmaceutical applications. However, the biosynthesis and bioactivity of circular bacteriocins still remain largely unknown. To investigate and gain more insights into the biosynthesis of circular bacteriocins and to achieve efficient production and characterization of bacteriocin variants, we developed an efficient cloning and heterologous expression system for clostridial circularin A and successfully produced this circular peptide in Lactococcus lactis NZ9000. We report three system formats with single plasmid or plasmid combinations to achieve successful cloning and functional production of circularin A in L. lactis. These systematic varieties enabled us to choose the appropriate method to efficiently obtain various constructs with desired properties. With the established heterologous systems in L. lactis, we performed several mutagenesis studies in the precursor peptide to study its structure/function relationships. The overlay activity assay revealed that these mutant variants had variable effects on different indicator strains: lysine substitution for certain glutamine residue(s) greatly decreased its bioactivity against Clostridium perfringens and L. lactis NZ9000, and alanine replacement for the cationic residues significantly reduced the activity against Lactobacillus sake ATCC 15521, whereas alanine substitution for the aromatic residues decreased its bioactivity against all three testing strains dramatically. Moreover, the conditions for bacteriocin production were optimized. Results show that supplementing the minimal medium with extra glucose (or sucrose) and immediate nisin-induction improved the peptide yield significantly. Briefly, we developed an excellent system for the production of circularin A and a wide range of variant peptides in a convenient host, as well as a method for fast detection of peptide production and activity. This system facilitated our mutagenesis studies which provided valuable insights into the effects of mutating specific residues on its biosynthesis and bioactivity, and will eventually enable more complex research into the biosynthesis of circularin A.